INFLUENCE OF NOISE ON PROFESSIONAL INCIDENCE OF WORKERS IN FOUNDRY SHOPS - A. M. Lazarenkov; S. A. Horeva (Литьë и металлургия, 2016)
Influence of noise on working in foundry shops is considered (distribution of occupational disease cochlear neuritis of an auditory organ by professions and indicators of incidence of working).